Eksplorasi Penggunaan Media Pembelajaran Games Book untuk Meningkatkan Minat Baca Peserta Didik Kelas 3 SD - Avika Septiana Hapsari; Yeni Nuraeni; Syahnia Maulida Fitria; Virna Dhia Ulhaq; Rizkia Putri Awalina (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
Education is an essential component in an individual’s life which plays a role in providing self-development, determining the future, and forming national identity. In the educational process, reading skills are an important aspect because reading is the key to gaining knowledge. A high interest in reading will encourage students to learn independently and broaden their horizons. However, interest in reading is often influenced by internal factors such as understanding the benefits of reading, and external factors such as the social environment and the availability of learning media. Games Book-based learning media is one solution to increase students’ reading interest. This media combines game elements with learning, creating an interactive and fun learning atmosphere. Games Books are also able to stimulate creativity, increase learning motivation, and support collaborative learning. In its implementation, this media is designed to attract students’ attention with educational games such as mazes, puzzles, puzzles and other games. As a result, the use of this media has proven to be effective in increasing students’ reading interest. This research aims to explore the potential of using Games Books in increasing students’ reading interest, especially at the elementary school level. With a creative educational approach, it is hoped that this media can make a positive contribution to the learning process, support the achievement of educational goals, and create meaningful learning experiences.